The Setting-Up Measure to Support Generational Renewal in Agriculture: The Italian Experience - Francesco Licciardo; Roberto Henke; Francesco Piras; Barbara Zanetti (World)
Since the 1970s, the issue of ageing farmers and generational renewal in agriculture has consistently attracted the attention of policymakers. However, despite successive reforms of the European Union Structural Funds, efforts to encourage young people to enter the agricultural sector remain largely focused on agricultural and rural policies, specifically on the First Settlement scheme. This paper highlights the role of the European Union’s rural development policy in supporting and encouraging generational renewal in agriculture. A qualitative analysis of the Italian case examining some of the demographic changes that have occurred within the agricultural system at the regional level has been conducted. The analysis is based on the comparison of policy implementations in different programming periods. Using data from the General Censuses of Agriculture and the Italian Agricultural Payments Agency—supplemented by the Annual Implementation Reports of the Italian Rural Development Programmes—the research traces the evolution of initiatives supporting young farmers. The main findings reveal a notable decline in the number of young people in the primary sector over the last decade, together with an ageing population of agricultural farmers. Measures to support young farmers under the Common Agricultural Policy appear to be ineffective in countering the ageing trend. There is scope for integrated policies to enhance the attractiveness and profitability of rural areas and to ensure long-term sustainable generational renewal in the agricultural sector.